Development and Design A Queue Service System Banyumudal Health Center Using the Waterfall Method - Azmi, Wifqi Wifakul; Nur, Yohani Setiya Rafika (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2025)
Puskesmas Banyumudal is a health care facility in Pemalang Regency, located at KM 1, Banyumudal, Jalan Raya Moga-Karangsari, Moga District, Central Java. This health center aims to improve the standard and equity of health services for all levels of society. one of the main obstacles that is often faced is the lack of management of patient queues that still use manual systems, causing long and irregular queues resulting in inefficient and ineffective patient waiting times. this research was conducted to build a more efficient and effective Banyumudal Health Center queue service system. by using the waterfall method, through this system, it is hoped that service efficiency will increase by reducing the duration of patient queues and improving better service quality. This method involves clear stages, starting from analyzing needs, designing designs, and testing. The results of the study show that the application of the waterfall method in the development of the Banyumudal health center queuing service system is able to improve queue management efficiently and effectively and provide information to patients regarding queue status, as well as facilitate health center officers and doctors in monitoring the queuing process. blackbox testing results show that all systems function properly according to predetermined specifications. thus, the queuing system designed is expected to have a positive impact on improving the quality of queuing services at the Banyumudal Health Center.